Bimtek Merdeka Belajar Untuk Pembekalan Guru Sekolah - Gunawan, Heri; Meizar, Abdul; Nugroho, Ahir Yugo; Sari, Ria Eka; Buyung, Adnan (Publikasi Pengabdian Masyarakat, 2022)
SMP Negeri 2 is one of the State Junior High Schools located in Hamparan Perak District, Deli Serdang Regency, North Sumatra Province. This school has approximately 20 teaching teachers. The school is located at Jalan Pasar 2, Tandam Hilir II Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra Province. Because it is a little far from the city, the development of technology in terms of teaching is still little known. Merdeka Learning is a policy program from the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud RI) which was launched by the Minister of Education and Culture of the Republic of Indonesia for the Advanced Indonesia Cabinet, Nadiem Anwar Makarim. The essence of freedom of thought, according to Nadiem, must be preceded by teachers before they teach it to students. Nadiem said, in the competence of teachers at any level, without a translation process of the basic competencies and existing curriculum, there will never be any learning that takes place. For this reason, the institution forms a team that will provide material on making moving animations for training at the school. The author as one of the presenter team uses power point slides in the form of presentations, direct practice of accessing the independent learning web application using each teacher's account. From before, the understanding to access and use the independent learning modules for approximately 20 teachers who attended the training was only 10%, but after attending the training it increased to 80%. Understanding is obtained by doing upload module tests, create classes, create quizzes and exams, and also absent students to teachers after being given the training. The training carried out by the Main Potential University Institution team is also an embodiment of the Lecturer's Tri Dharma, namely Community Service.